The effects hydroxyurea derİvatİve schİff bases on fatty acİds and lypophİlİc vİtamİns in liver of rats - Turkoglu, Semra; Parlak, Akif E.; Yildirim, Isil; Karagozoglu, Yusuf; Alayunt, Naci O. (Inst Materials Physics, 2014)
Schiff bases and their metal complexes have antiviral, antimicrobial, antitumoral, radical scavenging and antioxidant activities. In this study, effects of Schiff base ligand and i{dotless}ts metal complexes on the fatty acids and lyphophlilic vitamins of the liver of rats were investigated. The fatty acids of the liver were determined by GC and lyphophlilic vitamins of the liver determined by HPLC. The amounts of stearic acid (18:0), oleic acid (18:1) and monounsaturated fatty acids (MUFA) considerably decreased in the Mn, Ni and Zn complexes groups, whereas the amount of linolenic acid (18:3) and eicosatrienoic acid (20:3) considerably increased in the Ni an Zn complexes groups compared to the control group (P<0.01).However, there was no significant difference (P>0.05) in the amounts of arachidonic acid (20:4), docosahexaenoic acid (22:6), total saturated fatty acids (SFA) and polyunsaturated fatty acids (PUFA), total omega-3 and omega- 6 fatty acids between groups. The amounts of vitamin K1, vitamin D2 considerably increased (P<0.05) in the Mn and Ni complexes groups as compared to the control. It was observed that the amount of ?-tocopherol increased both in the Ni and Co complexes groups when compared to the control group but this increase was parallel to the amount in the same groups (P<0.05). As a result, it can be think that with the application of toxic metals such as manganese, cupper, nickel, cobalt, and zinc unsaturated fatty acids affected the activities of enzymes which are in the liver tissue and in charge in the fatty acid chain elongation.
Keywords: Fatty acid; Hydroxyurea Derivative Schiff base; Liver; Lypophilic vitamin; Rat